THE PRESENT STAGE OF POSITIONING OF THE REPUBLIC OF KAZAKHSTAN IN ENERGY ARCHITECTURE OF THE CASPIAN REGION - S. Smagulova (Вестник университета, 2017)
At the present stage participation of Kazakhstan in system of an energy cooperation in the Caspian region is very contradictory, connected as with internal economic problems, and development of economic integration in the former Soviet Union. In the article vectors of creation of the energy strategy of Kazakhstan in the Caspian region in difficult geoeconomic conditions are analyzed and generalized.